2011
DOI: 10.1159/000330800
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Rupture of Horseshoe Kidney

Abstract: We present the case of a 25-year-old male who came to the emergency room for pain and abdominal distension following trauma to the mesogastrium. A CT scan was performed, revealing a voluminous retroperitoneal hematoma with laceration of both inferior renal poles with regard to rupture of the isthmus of a horseshoe kidney. The patient presented anemization and increased pain, requiring selective embolization by means of arteriography of a branch of the right renal artery and placement of a double J stent due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
0
5
0
2
Order By: Relevance
“…The RAE could be used successfully even in the cases of anatomically abnormal kidney injury. Molina Escudero R. et al in 2012 reported about effective use of selective embolization by means of arteriography of a branch of the right renal artery and placement of a double J stent due to urinary extravasation in the lower left horseshoe kidney pole [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The RAE could be used successfully even in the cases of anatomically abnormal kidney injury. Molina Escudero R. et al in 2012 reported about effective use of selective embolization by means of arteriography of a branch of the right renal artery and placement of a double J stent due to urinary extravasation in the lower left horseshoe kidney pole [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The present patient appears to be only the eighth reported case of blunt force injury to a horseshoe kidney and the fifth with nonoperative management. The details of our search of the English language literature on the various types of management and outcomes of blunt force-injured horseshoe kidneys are shown in Table 1 [7][8][9][10][11][12][13]. The average age of blunt force injury to a horseshoe kidney patients was 31.75 years, and this occurred more commonly in male patients (7/8, 87.5%).…”
Section: Case Reports In Urologymentioning
confidence: 99%
“…Blunt force injury to this anomalous kidney is challenging with regard to nonoperative management, especially if it is a high-grade injury with active bleeding. From the literature review of blunt force horseshoe kidney injury, the average age is 31.75 years and occurred more common in male (87.5%) [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Следует отметить, что патологически измененная почка легче травмиру-ется, поэтому анамнез жизни должен быть собран. Считают [24,37], что почка с гидронефротической трансформацией, кистами, конкрементами, опухо-лью повреждается уже при минимальной травме, сообщения о травме подковообразной почки также не являются казуистикой [45,73,86].…”
unclassified
“…Необходимо отметить, что лечение травмы под-ковообразной почки проводится аналогично, с ис-пользованием консервативной терапии [86], эндо-васкулярной эмболизации [31,73,103], открытой операции [45].…”
unclassified